Ethical considerations of genetic manipulation in sport - Ehrbar, J. T. (The Sport Journal, 2015)
New technologies are currently being developed that will enable medical professionals to modify genes for medicinal purposes. As the process continues to be refined, the emergence of a controversial new use for this technology has ignited some serious debate. Scientists have submitted that genetic modification could potentially be used as a method of performance enhancement in sport. There are different schools of thought on this type of performance enhancement, and researchers and theorists have argued the advantages and disadvantages of using such a technology. These arguments are discussed in the present review. Though the ethical debate on this matter is in its infancy, a general consensus is that the allowance of genetic modification for the purpose of enhancing performance in sport will most certainly create a new look, along with new concerns, for sport in the future.